ResilienceBench-Operator: A Kubernetes Extension for Orchestrating Resilience Experiments on Microservice Applications - Aderaldo, Carlos M.; Mendonça, Nabor C. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2025: Anais do XXXIX Simpósio Brasileiro de Engenharia de Software, 2025)
Microservice-based applications often rely on resiliency patterns such as Retry and Circuit Breaker to mitigate the impact of failures in service-to-service communication. However, there is still limited tooling support for systematically and reproducibly evaluating the performance impact of these patterns in realistic deployment environments. This paper presents ResilienceBench-Operator, a Kubernetes native tool that orchestrates resilience experiments directly on microservice applications deployed in Kubernetes clusters. ResilienceBench-Operator is an evolution of the original ResilienceBench tool, which was focused on controlled environments with predefined client-server interactions. The new version introduces a fully declarative approach to define test spaces, automatically expands them into concrete test scenarios, injects failures, and configures resiliency strategies across real service dependencies. This paper describes the motivation, architecture, and main functionalities of ResilienceBench-Operator, and illustrates how it enables systematic evaluation of resiliency strategies in a representative microservice system. Demo video: https://youtu.be/ZSQcx6Ab37w .